Genetic association of toll like receptors and breast cancer: a novel approach toward countering the breast cancer tumor invasiveness and recurrence - Avishek Das; Avisek Banerjee (Egyptian Journal of Medical Human Genetics)
Abstract A diverse set of antigens is recognized by Toll-like receptors (TLRs), which are part of pattern recognition receptors in innate immunity. Humans possess 10 major types of TLRs that identify various molecular pattern molecules from bacteria to viral antigens. TLRs are highly conserved among humans and are located on the cell surface (e.g., TLR 2, 4, 6) as well as in intracellular compartments (e.g., TLR 7, 9). Breast cancer (BC), a leading global disease with a high survival rate in early stages, is particularly prevalent in India, accounting for 28.2% of all female cancers, with an estimated 216,108 cases by 2022 and increasing annually in the South East Asia region. It is projected to cause a death rate of over 61% by 2040 according to the American Cancer Society. Triple-negative BC is a prominent malignant form, while luminal types A and B are most common among women. Different TLRs play crucial roles against BC cells, with TLR4 and 9 extensively studied and found to be highly associated with tumor progression and metastasis. The tumor microenvironment, along with genetic and environmental factors, influences TLR expression, often reducing the likelihood of cancer growth via adaptor molecules like TRAF6 and IRAK. Allelic variations in TLRs are linked to different risk factors among populations. Extensive studies are needed to establish correlations between gene-disease associations and develop better diagnostic markers for detecting BC in the future.